Thyrotoxicosis Induced by Thyroid Involvement of Disseminated Aspergillus fumigatus Infection - Hornef, Mathias W. (American Society for Microbiology, 2000)
Aspergillus fumigatus is increasingly recognized as an important nosocomial pathogen in severely immunocompromised patients. Infection is difficult to diagnose antemortem and typically has a fatal outcome. Here we report the case of a cardiac transplant recipient with disseminated A. fumigatus infection which clinically presented as thyrotoxicosis due to massive involvement of the thyroid gland.